Spontaneous expectoration of tumor tissue in primary adenocarcinoma lung - Dixit, Ramakant (Avicenna J Med, 2021)
Spontaneous expectoration of the tissue fragments in primary lung carcinoma is an extremely unusual event. Expectoration of tumor fragments is a significant event that should not be ignored as it serves itself as a noninvasive tool to diagnose underlying malignancy if such samples are immediately preserved and subjected to histopathological examination. More so, expectoration of a large-sized fragment may provide substantial relief from the breathlessness. Reported here is the case of a middle-aged male patient with adenocarcinoma in the right lung, and mass extended up to trachea, who spontaneously coughed out pieces of tumor tissue.